การพัฒนาระบบบริหารสู่ความเป็นเลิศของโรงเรียนเอกชนสอนศาสนาอิสลามควบคู่วิชาสามัญ - มนัส บุญชม (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This research used a quantitative methodology. The purposes on studying the current situation and desirable situation of management system and development to management system toward excellence of private school simultaneously teaching Islamic and general education. There are 4 stages of research Methodology: 1) system analysis 2) system management design 3) system Validation and 4) system presentation. The study populations are 321 schools. The samples are 127 schools. Accounted for 76.9 percent of Informant are director deputy director, teacher of general education, teacher of Islamic studies, chairman of the school board, chairman of student council. Instruments included questionnaires interview forms and appropriate for assessing the feasibility of the of management system. The analysis used statistics from frequency, percentage, mean and standard deviation , the technique called Modified Priority Needs Index was applied. The research was found: 1) The current situation and desirable situation of management system toward excellence of private school simultaneously teaching Islamic and general education based on Malcolm Baldrige criteria for performance excellence; the highest average income is Leadership. The highest average of desirable situation income is Leadership. Index of needs (PNI[substitute Modified] ), all of average highest=0.18, The schools of Southern, maximum index of needs (PNI[substitute Modified]) were Measurement, Analysis, and Knowledge Management, PNI[substitute Modified] average =0.25, the second index of needs is Workforce Focus : average =0.22 and minimum index of needs (PNI[substitute Modified]) is Customer Focus : average =0.19. The schools of Central, maximum index of needs (PNI[substitute Modified]) is Workforce Focus : average=0.25, the second index of needs were Measurement, Analysis, and Knowledge Management, PNI[substitute Modified] average =0.24 and minimum index of needs (PNI[substitute Modified]) is Customer Focus : average =0.16. 2) Management system toward excellence of private school simultaneously teaching Islamic and general education. There are development 2 systems. 1) Management system for the school of Southern was Management system toward excellence of Private school simultaneously teaching Islamic and general education based focus on Measurement, Analysis and Knowledge Management and Operations Focus. 2) Management system for the school of Central was Management system toward excellence of Private school simultaneously teaching Islamic and general education subjects based on Operations Focus and focus on Measurement, Analysis and Knowledge Management.